Comparison of calcium ameliorants and coal ash in alleviating the effects of subsoil acidity on maize root development near Middelburg, Mpumalanga - Awkes, Meryl Mandy (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Soil Science))--University of Stellenbosch, 2010.